Fatigue behaviour of NiTi shape memory alloy scaffolds produced by SLM, a unit cell design comparison. (June 2017) - Speirs, M.; Van Hooreweder, B.; Van Humbeeck, J.; Kruth, J.-P.
Abstract: Selective laser melting (SLM) is an additive manufacturing technique able to produce complex functional parts via successively melting layers of metal powder. This process grants the freedom to design highly complex scaffold components to allow bone ingrowth and aid mechanical anchorage. This paper investigates the compression fatigue behaviour of three different unit cells (octahedron, cellular gyroid and sheet gyroid) of SLM nitinol scaffolds. It was found that triply periodic minimal surfaces display superior static mechanical properties in comparison to conventional octahedron beam lattice structures at identical volume fractions. Fatigue resistance was also found to be highly geometry dependent due to the effects of AM processing techniques on the surface topography and notch sensitivity. Geometries minimising nodal points and the staircase effect displayed the greatest fatigue resistance when normalized to yield strength. Furthermore oxygen analysis showed a large oxygen uptake during SLM processing which must be altered to meet ASTM medical grade standards and may significantly reduce fatigue life. These achieved fatigue properties indicate that NiTi scaffolds produced via SLM can provide sufficient mechanical support over an implants lifetime within stress range values experienced in real life.